2001
DOI: 10.1046/j.1365-3024.2001.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine efficacy of recombinant cathepsin D aspartic protease from Schistosoma japonicum

Abstract: Mice were vaccinated with recombinant Schistosoma japonicum cathepsin D aspartic protease, expressed in both insect cells and bacteria, in order to evaluate the vaccine efficacy of the schistosome protease. Mean total worm burdens were significantly reduced in vaccinated mice by 21-38%, and significant reductions in female worm burdens were also recorded (22-40%). Vaccination did not reduce fecundity; rather, we recorded increased egg output per female worm in vaccinated animals, suggesting a crowding effect. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 36 publications
3
37
1
Order By: Relevance
“…The authors proposed that the protective response was antibody mediated. An aspartyl protease isolated from Schistosoma japonicum, causative agent of schistosomiasis, has also been evaluated as a vaccine in a murine model of this disease (44). Immunization with the recombinant protein resulted in reduced worm burden in challenged mice but little to no effect in reducing the fecundity of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…The authors proposed that the protective response was antibody mediated. An aspartyl protease isolated from Schistosoma japonicum, causative agent of schistosomiasis, has also been evaluated as a vaccine in a murine model of this disease (44). Immunization with the recombinant protein resulted in reduced worm burden in challenged mice but little to no effect in reducing the fecundity of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine efficacy of recombinant cathepsin D aspartic protease from Schistosoma japonicum (Verity et al, 2001) and Haemonchus contortus (Longbottom et al, 1997) has been reported. Immunolocalisation experiments performed by the authors (Jolodar et al, unpublished data) indicated that the recombinant OV7A protein encoding an aspartic protease was predominantly associated with the hypodermis and inner membrane zone of the uterine wall of adult females.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Vaccination with recombinant forms of S. japonicum CatD in the mouse model of schistosomiasis achieved significant reductions in total worm burden across numerous trials. 13 RNA interference targeting the gene encoding S. mansoni CatD resulted in a lethal phenotype (growth retardation) and the reduction in the ability of the parasite to effectively digest Hb in vitro. 14 While it is possible to generate recombinant Sm-CatD for small-scale vaccine testing, high-yield expression of eukaryotic proteases is problematic.…”
Section: Introductionmentioning
confidence: 99%